PENGARUH SIMPANAN DANA PIHAK KETIGA TERHADAP RETURN ON EQUITY (ROE) DI PT BANK BJB, Tbk. PERIODE 2009 – 2016 - ., Sugiyanto (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2017)
This research aimed to determine how much of the influence Third Party Fund to Return On Equity (ROE) at PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk in the periods of 2009 – 2016. The research method used is descriptive method with quantitative approach. The data collection technique used is observations, interviews, and literature study. The analysis technique used is data correlation coefficient analysis pearson product moment, and coefficient of determination. Based on the result obtained correlation pearson product moment of -0,753 with significance level of 0,031 which means strong and negative influence, the value of determination coefficient of 0,567 which means the influence of third party fund to Return On Equity (ROE) of 56,7% while 43,3% influenced by other factors not examined. The problem which were found from research conducted such as: there was declined a considerable of deposits in 2016 ,for Rp13.199.420,00, the number of customers who have problems in fulfilling the obligations caused less selective and meticulous in analyzing the debtors. The suggestions from the writer are : 1) Perform server maintenance regularly so as not to interfere with disbursement, payment, and credit repayment, 2) More consideration the ability of customers in fulfilling the obligations to reduce credit risk.